2013
DOI: 10.1016/j.earlhumdev.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia in children

Abstract: Community-acquired pneumonia (CAP) remains a frequent cause of morbidity and mortality worldwide even in industrialised countries, and its incidence is highest among children aged <5 years. Over the last two years, three international guidelines have been updated with new evidence concerning the incidence, aetiology and management of childhood CAP, but there are still some major problems in standardisation. The main aim of this review is to consider the available data concerning the aetiology, diagnosis, evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
1
23
0
5
Order By: Relevance
“…Despite advanced diagnostic tests, a clinical algorithm has not yet been developed to clarify etiology in the child age group. Specifically, high coinfection rates (30 to 45%) accompanying viral CAP cases increase the difficulty of this situation (4,5). Unclarified CAP etiology is critical, since it leads to unnecessary use of antibiotics, elevated resistance, and increased health care expenses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite advanced diagnostic tests, a clinical algorithm has not yet been developed to clarify etiology in the child age group. Specifically, high coinfection rates (30 to 45%) accompanying viral CAP cases increase the difficulty of this situation (4,5). Unclarified CAP etiology is critical, since it leads to unnecessary use of antibiotics, elevated resistance, and increased health care expenses.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial agents are a less significant factor (10%-40%) (3). However, many studies published in the last ten years have reported that mixed viral/bacterial infections play a role in 45% of pediatric CAP cases (4). Similar signs and symptoms caused by these agents result in the failure of radiological findings to differentiate the agents and difficulties in the routine practice of invasive interventions, such as hemoculture, bronchoalveolar lavage (BAL), and lung needle biopsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zur Unterscheidung zwischen viralen und bakteriellen Pneumonien hilft das Labor (Leukozytenzahl, Differenzialblutbild, Blutsenkungsgeschwindigkeit, C-reaktives Protein [CRP]) oft nur wenig weiter [5]. Allerdings wird Procalcitonin mittlerweile eine gute Aussagekraft bzgl.…”
Section: Diagnoseunclassified
“…der Fragen, ob eine bakterielle Pneumonie vorliegt und wie lange diese antibiotisch zu behandeln ist, zugeschrieben [12]. Die Identifizierung des auslösen-den Pathogens gestaltet sich bei Kindern ebenfalls kompliziert, da Sputumproben nur von größeren Kindern gewonnen werden können [5]. Nasen-und Rachenabstriche von jüngeren Kindern sind ungeeignet, da diese häufig mit pneumonieauslösenden Bakterien besiedelt sind, diese jedoch keine klinische Relevanz haben [20].…”
Section: Diagnoseunclassified